2021
DOI: 10.5194/ms-12-471-2021
|View full text |Cite
|
Sign up to set email alerts
|

Lagrange-method-based dynamic analysis of multi-stage planetary roller screw mechanism

Abstract: Abstract. A rigid-body dynamic model of multi-stage planetary roller screw mechanism (multi-stage PRSM) is proposed in this paper. The structure of multi-stage PRSM is introduced and the motion analysis is presented. The total kinetic energy of the mechanism is calculated. The rotation of the screws and carriers is chosen as generalized degrees of freedom. The generalized forces and motion equations of multi-stage PRSM are derived using the Lagrange method. The transient and steady-state behaviours of multi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The results obtained from the approach proved that the frictional moment acting on the screw, roller and carrier had a great influence on the transmission efficiency of the mechanism under light or heavy external load. Taking interfacial friction and the Lagrange method into consideration, Li et al 97 proposed a rigid-body dynamic model of the multi-stage PRSM and systematically analyzed friction coefficients and thread pitches under different transmission situations. The simulation results showed that the friction coefficients and contact force of the screw had a significant impact on the transmission efficiency.…”
Section: Transmission Characteristicsmentioning
confidence: 99%
“…The results obtained from the approach proved that the frictional moment acting on the screw, roller and carrier had a great influence on the transmission efficiency of the mechanism under light or heavy external load. Taking interfacial friction and the Lagrange method into consideration, Li et al 97 proposed a rigid-body dynamic model of the multi-stage PRSM and systematically analyzed friction coefficients and thread pitches under different transmission situations. The simulation results showed that the friction coefficients and contact force of the screw had a significant impact on the transmission efficiency.…”
Section: Transmission Characteristicsmentioning
confidence: 99%
“…The exploration of nonlinear dynamics [68] in PRSMs and BSMs has been a focal point of recent research, aiming to enhance the understanding of their operational behaviors under various loading and motion conditions. This review synthesizes the contributions from a selection of studies that delve into the dynamic equations of motion, nonlinear modeling, and the implications of these dynamics on the performance and reliability of PRSMs and BSMs [69].…”
Section: Nonlinear Dynamicsmentioning
confidence: 99%
“…A series of research on PRSM have been published internationally with focus on theoretical advancement including the design method [9], motion characteristics Page 2 of 16 Qiao et al Chinese Journal of Mechanical Engineering (2022) 35:87 [10], dynamics [11,12], thermal behavior [13], and load distribution [14,15]. However, only a few studies have been conducted on the design, kinematic characteristics, and dynamic analysis of the RPRSM, which is significantly important for EMAs in the aerospace industry.…”
Section: Introductionmentioning
confidence: 99%